COVID-19 and mortality in doctors. Issue 6 (November 2020) - Iyengar, Karthikeyan P.; Ish, Pranav; Upadhyaya, Gaurav Kumar; Malhotra, Nipun; Vaishya, Raju; Jain, Vijay Kumar
Abstract: Background and aims: COVID-19 disease appear to have been associated with significant mortality amongst doctors and health care workers globally. We explore the various risk factors associated with this occupational risk, especially focusing on India. This may elucidate lessons to protect these frontline workers during the COVID-19 pandemic. Methods: We carried out a comprehensive review of the literature using suitable keywords such as 'COVID-19', 'pandemics', 'physicians' 'mortality' and 'health personnel' on the search engines of PubMed, SCOPUS, Google Scholar and ResearchGate in the month of July 2020 during the current COVID-19 pandemic and assessed mortality data. Results: Mortality in health care professionals has been on the rise. The countries which faced the pandemic in the early months of 2020 have had a huge surge in mortality amongst doctors due to COVID-19. India continues to show a rising trend in COVID-19 cases, however although compared to the western world India has seen a comparatively favourable statistic. Male gender, elderly doctors and those belonging to Black, Asian, and Minority Ethnic (BAME) community seem to be predisposing factors in the western world. Conclusion: COVID-19 has been associated with an increased mortality in doctors and health care workers. Until an effective cure/vaccine is developed, risk assessments at work, mitigating confounding factors, adequate supply of personal protective equipment (PPE) and enhanced protection against infection are necessary to protect health care professionals on the coronavirus frontline. Otherwise this occupational risk can lead to further untimely mortality and become another unintended consequence of the COVID-19 pandemic. Highlights: COVID-19 has been associated with increased mortality amongst doctors and health care workers. Multifactorial reasons can be attributed for increased mortality seen in doctors during the COVID-19 pandemic. Risk assessment, enhanced protection and infection prevention measures at work are necessary to protect doctors.